2021
DOI: 10.1002/vzj2.20109
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic characterization of soil compaction using integrated electrical resistivity and X‐ray computed tomography

Abstract: Modern agricultural practices can cause significant stress on soil, which ultimately has degrading effects, such as compaction. There is an urgent need for fast, noninvasive methods to characterize and monitor compaction and its impact on hydraulic processes. Electrical resistivity tomography (ERT) is a well-established method used for the assessment of soil hydraulic properties due to its high temporal resolution and sensitivity to changes in moisture content and salinity, whereas X-ray computed tomography (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Assuming that differences in macroporosity are correctly inferred, this implies an increase of connectivity of soil aggregates as a result of soil compaction (see also Cimpoiasu et al., 2021). Such increases in aggregate connectivity for compacted soils are predicted when studying the dynamics of soil aggregate contacts in response to compaction controlled by soil rheology (see e.g., Or & Ghezzehei, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that differences in macroporosity are correctly inferred, this implies an increase of connectivity of soil aggregates as a result of soil compaction (see also Cimpoiasu et al., 2021). Such increases in aggregate connectivity for compacted soils are predicted when studying the dynamics of soil aggregate contacts in response to compaction controlled by soil rheology (see e.g., Or & Ghezzehei, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In their article "Toward high-resolution agronomic soil information and management zones delineated by groundbased electromagnetic induction and aerial drone data," von Hebel et al (2021) focus on the integration of soil EC a maps generated using a classical EMI survey with time-lapse aerial data to generate management zones at the size of agricultural machinery. They show that the information content in aerial data is highly time dependent and that for the analyzed case studies, no added value was observed when aerial data were added to the EMI data to delineate management zone.…”
Section: Core Ideasmentioning
confidence: 99%
“…In “Hydrodynamic characterization of soil compaction using integrated electrical resistivity and X‐ray tomography,” Cimpoiaşu et al. (2021) focus on the urgent need to develop fast techniques to characterize and monitor soil compaction. They used the combined capabilities of small‐scale X‐ray tomography and larger scale ERT tomograms to investigate the effect of different levels of compaction on soil hydrodynamic functioning.…”
mentioning
confidence: 99%